MI-SPE, M-SPE AND M-SPD RECENT APPLICATION ON SOLID PHASE EXTRACTION FOR COMPOUND EXTRACTION OF COMPLEX MATRICES - gopalan, sharimina venu; Hasanah, Aliya Nur (International Journal of Applied Pharmaceutics, 2019)
Solid Phase Extraction is a method used for extraction, purification of compounds contained in complex matrices and purification of samples in the fields of industry, pharmacy, and toxicology analysis. This review represents the recent advances of solid phase extraction from different mode of separation which are the most commonly used in recent days such as molecular imprinting solid phase extraction (MISPE), magnetic solid phase extraction (MSPE) and matrix solid phase dispersion (MSPD). In this review, the applications of MISPE in the analysis of agrochemicals such as herbicides, fungicides and insecticides are summarized. This review also states preparation of various magnetic composites (MSPE) based on graphene and its application as adsorbents in pre concentrating natural mixes, organic macromolecules. Besides this, this review summarizes the application of MSPD in biological, food, and environmental samples, including both organic and inorganic analyte.